The Relationship between Mother Pregnancy at a Young Age and the Emotional Development of Children Aged 3-5 Years - Reti Agung Ariyani; Yessy Nur Endah Sary; Tutik Ekasari; Nova Hikmawati (KHD Production, 2023)
The prevalence of emotional and behavioral disorders in preschool children is relatively high. One factor influencing children's emotional development is the mother's age during pregnancy. This study aimed to determine the relationship between maternal pregnancy at a young age and the emotional development of children aged 3-5 years. This study used a cross-sectional survey approach. The research subjects were all pregnant women and comprised 64 respondents, taken by simple random sampling. The independent variable is the emotional development of children aged 3-5 years as measured using the SDQ questionnaire. The dependent variable, namely the mother's age, was measured using a questionnaire. Data collection included coding, editing, data entry, and tabulation, then analyzed using a computer with chi-square. Of the 64 respondents studied, 54 respondents (84.4%) were pregnant women aged <20 years and experienced abnormal child emotional development, and 52 respondents (81.3%). The correlation test results between the mother's age during pregnancy and the child's emotional development obtained a coefficient of 0.565 with a significance value of 0.001. It can be concluded that a relationship exists between maternal pregnancy at a young age and the emotional development of children aged 3-5 years. Suggestions for adolescents, families, and health workers not to get married before the age of 20 so that there are no disturbances in the emotional development of children aged 3-5 years.